Політика США щодо Куби в умовах розрядки міжнародних відносин (1969 – 1979 рр.) - Касаткіна, Катерина Андріївна; Kasatkina, K. (My University, 2020)
У статті здійснена спроба проаналізувати особливості політики США щодо Куби в умовах розрядки міжнародних відносин у 1969 – 1979 рр. Основну увагу спрямовано на аналіз факторів, що вплинули на формування політики президентів Р. Ніксона, Дж. Форда і Дж. Картера щодо режиму Ф. Кастро та визначили характер якісних змін в означений період. Висвітлена робота американських дипломатичних представництв, державних відомств та установ щодо налагодження співпраці між двома країнами. У результаті проведеного дослідження авторка дійшла висновку, що політика США щодо Куби в умовах розрядки мала хвилеподібний характер, що було пов’язано не тільки зі специфікою американсько-радянських відносин у 1969 – 1979 рр., але й з особистим ставленням керівництва США до Ф. Кастро та перспектив майбутніх відносин у рамках латиноамериканського регіону.The article is an attempt to analyze the peculiarities of the U.S. policy towards Cuba during Détente (1969-1979). Particular attention is paid to factors which influenced on the formation of the U.S. Presidents` policy towards Fidel Castro`s regime and determined the nature of its qualitative changes in the given period. There is also described the work of American diplomats, the U.S.government departments and agencies on the establishment of cooperation between Washington and Havana. As a result of the research the author comes to the conclusion, that peculiarities of the U.S. Policy towards Cuba during Détente had a wavy character. That was due not only to the specifics of American-Soviet relations, but also to the personal attitude of the American leaderships to F. Castro. President Nixon was not ready to extend the principles of detente to Cuba as an ally of the Soviet Union. He continued the covert subversive political activities of previous American administrations. Such actions had led to an increase in Cuba's dependence on Moscow. At the beginning of G. Ford's presidency came a period of "thaw" in US-Cuban relations. The president maintained covert ties with the Castro`s government and eased US sanctions in Latin America. However, Cuba's active policy in Africa and its participation in the war in Angola put an end to Gerald Ford's initiative to normalize relations between the countries. President Jimmy Carter made an attempt to begin negotiations for resuming diplomatic relations with Castro`s regime. The escalation of military conflicts in Africa demonstrated the unity of the political position of the USSR and Cuba, which stopped the positive dynamics of US-Cuban relations. After the end of Detente, Washington returned to traditional approaches in its policy towards Havana.
The US policy towards Cuba during detente
Keywords: США; Куба; розрядка; Дж. Ніксон; Дж. Форд; Дж. Картер; Ф. Кастро; USA; Détente; Richard Nixon; Gerald Ford; Fidel Castro